2020
DOI: 10.3390/agriculture10030056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Increased Light Intensity on the Acceptance of a Solid Lying Area and a Slatted Elimination Area in Fattening Pigs

Abstract: Animal welfare labels have been introduced to improve housing conditions in conventional pig systems. Animal welfare should be increased by, e.g. offering a well-accepted and comfortable solid lying area. This study investigates the effect of bright light from an LED spotlight in the slatted area on lying and elimination behavior of fattening pigs. It was tested for two pen designs different in feeder and arrangement of the slatted area with 18 pigs per pen. The study took place in two different compartments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…Accordingly, Studnnitz et al (2007) concluded that in order to be a suitable rooting material the material must stimulate the exploratory behaviour of pigs for an extended length of time; moreover, exploratory behaviour in pigs is more stimulated by materials that are complex, changeable, destructible, manipulable, and contain sparsely distributed edible parts. In the present study, a significant effect of the pen location (indoor vs outdoor) on the lying behaviour was found, as a higher percentage of pigs laid on the dark area (indoor), which is in agreement with Opderbeck et al (2020). In July, with hotter temperatures than August, pigs lied down and were less likely to engage in aggressive behaviour, in line with Velarde and Geers (2007).…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, Studnnitz et al (2007) concluded that in order to be a suitable rooting material the material must stimulate the exploratory behaviour of pigs for an extended length of time; moreover, exploratory behaviour in pigs is more stimulated by materials that are complex, changeable, destructible, manipulable, and contain sparsely distributed edible parts. In the present study, a significant effect of the pen location (indoor vs outdoor) on the lying behaviour was found, as a higher percentage of pigs laid on the dark area (indoor), which is in agreement with Opderbeck et al (2020). In July, with hotter temperatures than August, pigs lied down and were less likely to engage in aggressive behaviour, in line with Velarde and Geers (2007).…”
Section: Discussionsupporting
confidence: 92%
“…The pigs in this design had the opportunity to eliminate as far as possible away from the feeding, as they seem to prefer it [7,53]. This experience had already been acquired in previous experiments of this project with similar pen designs [20].…”
Section: Effect Of the Pen Designmentioning
confidence: 89%
“…The pigs showed more resting behavior in areas with dimmer light intensity [18,19] and used the areas with high light intensity mainly for elimination [19]. A previous experiment of our group showed that a high light intensity in the slatted (designated) elimination area leads to more pigs lying on the solid lying area [20].…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies have investigated the various direct and indirect effects of light on the animal organism. The results showed that light can influence, among other things, the productivity, e.g., weight gain, feed intake and feed conversion, and general behaviour displayed by pigs [ 1 , 2 , 3 , 4 ]. However, care must be taken to ensure that the type of lighting does not have any harmful effects on the animal.…”
Section: Introductionmentioning
confidence: 99%